Radar Characterization of Salt Layers in Europa's Ice Shell as a Window Into Critical Ice‐Ocean Exchange Processes - N. S. Wolfenbarger; D. D. Blankenship; D. A. Young; K. M. Scanlan; C. J. Chivers; D. Findlay; G. B. Steinbrügge; K. Chan; C. Grima; K. M. Soderlund; D. M. Schroeder (Geophysical Research Letters)
Abstract The potential habitability of Jupiter's moon Europa has motivated two missions: NASA's Europa Clipper and ESA's JUpiter ICy moons Explorer (JUICE). Both missions are equipped with ice‐penetrating radars which will transmit radio waves into the subsurface, recording reflections from interfaces defined by contrasts in ice shell dielectric properties. Assuming an MgSO4 ocean, we show that salt layers, formed through the freezing of subsurface liquid water reservoirs, can be detected by ice‐penetrating radar instruments on Europa Clipper and JUICE. Furthermore, because these features are thermodynamically stable within the minimally attenuating portion of Europa's ice shell, referred to here as the “pellucid region,” they could produce brighter reflections than deeper liquid water interfaces. We demonstrate how ice‐penetrating radar measurements of salt layer thickness could establish lower bounds on the parameter space of possible initial reservoir thickness and salinity, constrain the origin of reservoirs (ice shell melt vs. ocean injection), and—if sourced through ocean injection—the ocean salinity.